DETERMINANTS OF CONSUMERS’ BRAND SWITCHING BEHAVIOR IN THE PURCHASE OF MINERAL WATER PRODUCTS IN MANADO CITY - Kawengian, Rico Reski (FEB Universitas Sam Ratulangi Manado, 2015)
Business of bottled mineral water is more appealing, companies have to keep maintaining their customers to prevent them on switching to another brand by analyzing what factors determines consumers switch brand. This research is conducted in Wanea sub-district Manado, North Sulawesi.The objectives of this research are to analyze the determinants of consumer brand switching behavior in the purchase of mineral water products partially and simultaneously. This research is the causal type of research where it will investigate the influence of elements on consumer brand switching behavior. Use multiple regression models to answer the research problem. The population in this study is a consumers of mineral water products, whereas samples taken by each respondent 100 respondents. The hypothesis testing, this research conduct a conclusion of there is a significant influence of Price, Promotion, Brand Image, and Brand commitment simultaneously and partially on Consumers Brand Switching behavior. This study reveals that brand image of mineral water products has a strong influence on consumers brand switching behavior because consumers’ in Manado city do not want to buy a product that have a bad image whether on their product or company itself because it will affect the both performance. Keywords: price, promotion, brand image, brand commitment, brand switching.